Who Is the Customer? On Multiple-Customer Representation in Supply Chains - Benedikte Borgström; Luis Araujo; Susanne Hertz (Logistics, 2025)
Background: Customer orders are key in developing logistics processes and in strategic developments of customer orientation. This paper investigates the notion of customer orientation. In the literature, the concept of customer is underdeveloped in that it is seen as a single object rather than how it is enacted in multiple ways. The study examines a customer-oriented production process managed in the supply chain of an automotive manufacturer. Methods: Based on a longitudinal study we explain what constitutes customer knowledge and what processes are involved in constructing this knowledge. Results: The study shows that in a supply chain, multiple versions of customers coexist and overlap that have implications on how multiple-customer orientation is performed and aligned in the supply chain. Conclusions: We find that customer representations proliferate as a result of multiple objectives; we demonstrate what objects and assemblages bring particular customer representation to life and show that these are used to shape customer orientation.